Volumetric properties of waste-modified asphalt mixtures through marshall stability - Wan Noor Hin, Mior Sani (Popular Scientist Publisher, 2025)
The rising needful for sustainable road construction materials yield to extensive research on asphalt modifi cation using waste materials such as industrial and agricultural, therefore this study explores the use of palm oil fuel ash (POFA), garnet waste, and sawdust as individual modifi ers to enhance the volumetric and mechanical properties of asphalt mixtures. The waste materials were individually mixed with 60/70 PEN asphalt binder at varying proportions of 0%, 3%, 6%, and 9%. The modifi ed mixtures were evaluated through the Marshall stability test, focusing on volumetric properties, voids in total mix (VTM), voids in the mineral aggregate (VMA), and voids fi lled with asphalt (VFA). The results validated that belnding individual waste materials signifi cantly enhanced the stability of asphalt mixtures compared to the control sample, with the 6% POFA modifi cation achieving the highest stability at 14.78 kN followed by 3% garnet waste (13.15 kN) and 3% sawdust (14.23 kN). The VTM and VMA values decreased with increasing waste content, indicating improved densifi cation and binder adhesion, while VFA increased, reflecting better asphalt retention within the aggregate structure. This study highlights the feasibility of utilizing individual POFA, garnet waste, and sawdust as sustainable alternatives in asphalt mixtures, offering potential cost savings and reducing reliance on virgin materials. The modifi ed mixtures exhibited satisfactory volumetric and mechanical properties, indicating their suitability for road applications, particularly in low to medium traffic pavements. However, further research is necessary to optimize the combination of these waste materials and assess their long-term durability, moisture susceptibility, and performance under diverse climatic and traffic conditions. The successful integration of these waste materials into asphalt pavements could contribute to more sustainable infrastructure development while ensuring compliance with engineering standards and road performance requirements.